Evaluation of Pharmacokinetics and Pharmacodynamics of Deferasirox in Pediatric Patients - Laura Galeotti; Francesco Ceccherini; Carmen Fucile; Valeria Marini; Antonello Di Paolo; Natalia Maximova; Francesca Mattioli (MDPI AG, 2021)
Background: Deferasirox (DFX) is commonly used to reduce the chronic iron overload (IO) in pediatric patients. However, the drug is characterized by a large pharmacokinetic variability and approximately 10% of patients may discontinue the treatment due to toxicities. Therefore, the present retrospective study investigated possible correlations between DFX pharmacokinetics and drug-associated toxicities in 39 children (26 males), aged 2-17 years, who underwent an allogeneic hematopoietic stem cell transplantation. Methods: IO was diagnosed by an abdominal magnetic resonance imaging and DFX was started at a median dose of 500 mg/day. DFX plasma concentrations were measured by a high performance liquid chromatographic method with UV detection and they were analysed by nonlinear mixed-effects modeling. Results: The pharmacometric analysis demonstrated that DFX pharmacokinetics were significantly influenced by lean body mass (bioavailability and absorption constant), body weight (volume of distribution), alanine and aspartate transaminases, direct bilirubin, and serum creatinine (clearance). Predicted DFX minimum plasma concentrations (Ctrough) accounted for 32.4 ± 23.2 mg/L (mean ± SD), and they were significantly correlated with hepatic/renal and hematological toxicities (p-value < 0.0001, T-test and Fisher's exact tests) when Ctrough threshold values of 7.0 and 11.5 mg/L were chosen, respectively. Conclusions: The population pharmacokinetic model described the interindividual variability and identified Ctrough threshold values that were predictive of hepatic/renal and hematological toxicities associated with DFX.